Sistem Informasi Profil Desa Berbasis Website (Studi Kasus : Desa Fatuana , Kecamatan Insana, Kabupaten TTU) - Naif, Kefin Gonsalves Batistita; Nababan, Darsono; Risald; Fetronela Rambu Bobu (JITU, 2024)
Fatuana Village is a village located in Insana District, TTU Regency, East Nusa Tengara Province. This village has a fairly large area and a very dense community, apart from that it also has good internet access, but Fatuana village does not yet have a village profile information system so many people do not know about Fatuana Village. Therefore, the aim of this research is to build an information system for the Fatuana village profile so that the community can access information about Fatuana village while also making it easier for the Fatuana village to serve the community by providing information quickly. This research applies the waterfall method as a system development method and uses PHP as a programming language in building the Fatuana village profile information system. This research produced a Fatuana village profile information system in accordance with community needs and has been successful in testing the system.